Hubungan Frekuensi dan Durasi Penggunaan Instagram Dengan Perilaku Pemilihan Makanan Jajanan Pada Remaja - Ravi Masitah; Ni Putu Eny Sulistyadewi (Politeknik Negeri Jember, 2021)
Instagram is a medium that is widely used by teenagers to upload or search for various snacks menu information. Frequency and duration of use instagram will affect the behavior of snack choice. Applying good behavior can help teenagers to fulfill their nutritional needs but bad behavior can cause health problems. The study aims to analyze the effect of the utilization frequency and duration of use instagram on the behavior of snack choice in teenagers. This research was quantitative descriptive with cross-sectional design. The sample was 91 teenagers aged 14-16 years, the selection was by purposive sampling. Data were analyzed by using chi-square test with SPSS. The results showed that there was a relationship between frequency and duration of use instagram on the behavior of snack choice in teenagers with p-value (0,000) <0.05. Keywords: frequency and duration of use instagram, snack choice behavior, teenager